2020
DOI: 10.1155/2020/9606807
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Surgical Management of Gastrointestinal Schwannomas

Abstract: Objectives. Schwannomas are tumors arising from Schwan cells of the neural sheath. Gastrointestinal schwannomas (GS) are rare and easily confused with a heterogeneous group of neuroectodermal or mesenchymal neoplasms. The aim of the present study is to analyze the clinicopathological features, surgical management methods, and long-term prognoses of GS patients. Methods. Between August 2004 and July 2019, 51 patients with GS were treated at the Peking Union Medical College Hospital. The medical records were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…According to the literature, the prevalence of GS is one in every 45 patients with GIST [ 5 ]. It has also been reported that GS is more common in female patients aged 40–60, with a male to female ratio of about 1:2 or higher [ 6 ]. The average age of patients in this study was 59 years old, and the male to female ratio was approximately 1:2, which was consistent with the findings of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the prevalence of GS is one in every 45 patients with GIST [ 5 ]. It has also been reported that GS is more common in female patients aged 40–60, with a male to female ratio of about 1:2 or higher [ 6 ]. The average age of patients in this study was 59 years old, and the male to female ratio was approximately 1:2, which was consistent with the findings of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is good because of the predominant benign nature of the tumor. Lymph-nodal involvement and/or hepatic recurrences are observed in very rare colorectal ‘malignant’ schwannomas (better termed as malignant peripheral nerve sheath tumor) [ 33 ]. Notably, colorectal schwannomas are sporadic, not associated with neurofibromatosis I or II (NF1 and NF2).…”
Section: Rare Tumors Of Colon and Rectummentioning
confidence: 99%
“…The appropriate surgical approach depends on tumour location and size, as well as the location of surrounding organs. 7 As these tumours are benign, radiotherapy and chemotherapy are not needed. 2 In 2015, a comprehensive review gathered 137 cases of gastric schwannomas and showed no cases of recurrence after a follow-up period ranging from 1 to 336 months.…”
Section: Images In…mentioning
confidence: 99%
“…Incomplete margins are the main cause of recurrence. 7 Regular follow-up with CT is not recommended. 6 Contributors FM and LT had the idea of the study.…”
Section: Images In…mentioning
confidence: 99%